About face : rethinking face for 21st century mission - Flanders, Christopher L. (Christopher Lane), 1965-- (Eugene, Oregon : PICKWICK Publications, 2011)
Past uncritical views of "face", furtively attaching to the theology of the Thai church have been detrimental for its life and mission and may account for the persistent Thai perception of Christianity as a foreign, Western religion, but this study gives hope that a self-conscious engagement of face can create a reversal. The "about face" proposal of this study intends to legitimate face as an issue of explicit theological reflection in the Thai context and to seek ways of assessing face from a Christian perspective in a contextualized soteriology that can be put to use in the Thai Christian community. To engage Thai face as Christian believers is to discern how the honor/glory of God in the face of Christ transforms our faces. To bring issues of face to the center of discipleship in the Thai context must surely mean understanding the shape of the prevalent Thai cultural model of face, the specific logic of face, and the specific dynamics of face claim-rights. These must be set alongside the orienting motifs of the imago Dei, the Face of God/Christ, and biblical honor dynamics. By investigating the ways Jesus himself engaged in the face game, we may discern through the guidance of the Holy Spirit the ways we should affirm, reorient, or subvert the various dimensions of Thai face. The early Christian response to honor was not a categorical rejection but a creative reformulation and reorientation of honor and shame through the new lenses of God's salvific activity. In becoming part of a Christian community, the person being remade in the likeness and image of God, the ecclesial self, receives a new account of face. This new self is part of a narrative that forms out new facework strategies. In particular this new face in Christ sets new terms for face claim-rights so that face may no longer be a mask behind which pride, selfishness and abusive power operate. If face is an enactment between the self and others based upon the specific logic of a claim-right, the new narrative into which our selves are drawn transfor
pt. 1. The loss of face. Cultural disconnect and the foreignness of Thai Christianity --Sources of prosopagnosia (loss of face) : the modern western self --Sources of prosopagnosia (loss of face) : the misconstrual of honor, guilt, and shame --pt. 2. Recovering face. Face and facework theory --Theoretical reflections on Thai face --A description of Thai face --pt. 3. Preserving face. Theological anthropology and a Christian understanding of face --A theological framework to orient face --Reconceiving the soteriological task --Salvation in the context of Thai face --Conclusions and recommendations.
Includes bibliographical references and index
Keywords: Missions -- Thailand; Christianity and culture -- Thailand; Honor -- Religious aspects -- Christianity; Honor -- Thailand; Christianity -- Thailand; Missions -- Theory; Tai (Southeast Asian people) -- Missions; Intercultural communication -- Religious aspects; Interpersonal relations -- Religious aspects